Transcriptional analysis for cholesterol-lowering effects of marine Lactobacillus plantarum Lp10 isolated from kelp. (March 2021) - Ye, Zhi-Wei; Guo, Tian-Fen; Tang, Can; Yuan, Yue; Zhao, Yi; Lu, Jun; Lin, Jun-Fang; Guo, Li-Qiong
Abstract: Lactobacillus plantarum, which exerts a variety of probiotic functions, has been recognized as a supplement for human foods with a widespread application. In this work, the cholesterol-lowering mechanisms of marine L. plantarum Lp10 were investigated by combining the analyses of transcriptome and quantitative real-time PCR. Results indicated that bile salt hydrolase (BSH) activity and extracellular polysaccharides (EPSs) adsorption were both responsible for cholesterol reduction. In this process, 11.1 million clean reads and 384 differentially expressed genes, including 79 up-regulated genes and 225 down-regulated genes, were obtained by transcriptome analysis. It was considered that EPS adsorption was mainly responsible for the cholesterol reduction without the influence of bile salt. Further analysis showed that the co-precipitation of cholesterol and deconjugated bile acids induced by BSH1 and BSH2 may play important role in the tolerance and reduction of cholesterol of strain under the stress condition with bile salt, in which, interestingly, the expressions of bsh3 and bsh4 were suppressed. In conclusion, the cholesterol-lowering mechanisms of marine L. plantarum Lp10 was investigated and it was considered as a potential strain for the application in cholesterol reduction. Highlights: Marine Lactobacillus plantarum Lp10 has significant cholesterol-reducing activity. Transcriptome was performed to analyze the cholesterol reduction of strain Lp10. EPS adsorption of Lp10 accounted for the cholesterol reduction in MRS-Cho medium. bsh1 and bsh2 of Lp10 were beneficial to cholesterol reduction in MRS-CB medium.